STONE FREE RATES OF KIDNEY STONE WAS LOWER THAN THE ONE OF URETER STONE PATIENTS MANAGED BY ESWL AND THE ONE OF URETER STONE MANAGED BY URETEROLITHOTRIPSY - Zamzami, Zuhirman (Indonesian Urological Association, 2018)
Objective: To evaluate the stone free rates of kidney and ureter stone patients managed by Extracorporeal Shockwave Lithotripsy (ESWL), and the ureter stone free rate managed by ureterolithotripsy. Material & method: We reviewed the medical records of kidney and ureter stone patients managed by ESWL and ureter stone patients managed by ureterolithotripsy in Arifin Achmad Regional General Hospital Pekanbaru Riau Province, Indonesia, from January 2010 - December 2016. ESWL and ureterolithotripsy stone free rates were examined by the control of KUB röngents. Results: There were 891 kidney and ureter stone patients consisting of 325 (36.5%) were kidney stone patients and 566 (63.5%) were ureter stone patients. The pyelum stones were the most (78.2%) in kidney stones and the lower ureter stones were the most (57.2%) in ureter stones. There were more male patients than the female ones in which most of the patients were in the group age of 49-59 years. The amount of patients increased each year. The kidney stone free rate managed by ESWL was lower (71.7%) than ureter stone free rate (84.1%) by ESWL, while the stone free rate of ureter stone patients managed by ureterolithotripsy was 100%. Conclusion: The ESWL stone free rate of the kidney stone patients was lower than the one in ureter stone patients while the ureterolithotripsy stone free rate was 100%.